Anticancer activity and high content screening of New 6 substituted-5,6-dihydrobenzo[4,5]imidazo[1,2-c]quinazoline derivatives - Ali Hasan, Hiba; Salman, Afrah; Abdulmalek, Emilia (A and V Publication, 2021)
Pursuing our interest in bioactive heterocyclic compound, two benzoimidazoquinazoline derivatives were synthesised using both microwave-assisted and classical heating methods. Structures of the compounds were confirmed by standard spectroscopic methods and elemental analysis. The target scaffolds were incidentally found to emit blue light when exposed to ultraviolet light. Consequently, a photoluminescence characterization was carried out as a part of characterization protocol. The anticancer activities of the benzimidazoquinazoline compounds were investigated using both methylthiazol tetrazolium (MTT) and the high content screen (HCS) assays against liver hepatocellular cells. The results showed a significant reduction in the inhibitory concentration of the cancer cells by 1 and 2.6 fold when exposed to compounds (3a) and (3b), respectively. The high content screen (HCS) was conducted for compound (3b) and the results showed high toxicity towards the cancer cells.